HAK ASASI MANUSIA TERHADAP KAUM LESBIAN, GAY, BISEKSUAL DAN TRANSGENDER (LGBT) DALAM PERSPEKTIF HUKUM INTERNASIONAL DAN HUKUM NASIONAL INDONESIA - Nurul Kamila; Sutiarnoto Sutiarnoto; Jelly Leviza (Journal of USU International Law, 2020)
ABSTRACT Nurul Kamila* Dr. Sutiarnoto, SH, M. Hum** Dr. Jelly Leviza, SH. M. Hum*** This study discusses the existence of lesbians, gays, bisexuals and transgender people (LGBT) in International Law and Indonesian National Law. Therefore, this study raises issues regarding: How the regulation of International Law on the existence of human rights of LGBT people, How is the regulation of national law on the existence of LGBT people and how is the comparison of Indonesian national law and International Law about the existence of the LGBT community. Thistype of research is a normative juridical research that is research conceptualized as a rule or norm based on statutory regulations. The results of research and discussion explain the regulation of International Law on the existence of human rights of LGBT people still leading to general provisions on human rights in international human rights instruments such as the UDHR and ICCPR. Then the Office of the United Nations High Commissioner for Human Rights established 5 state obligations towards LGBT people, and the formulation of the Yogyakarta Principles that addressed the rights of LGBT people. International legal instruments that specifically regulate LGBT issues do not exist, national legal regulations regarding the existence of LGBT people in Indonesia are also not found. Nevertheless, LGBT is fundamentally contrary to the Marriage and Pancasila Laws. Even though the 1945 Constitution says that every person has the right to marry and continue their descent, same-sex marriage cannot be carried out because it contradicts Article 2 of the Marriage Law and Pancasila values. iiKeywords: Human Rights, Lesbian, Gay, Bisexual and Transgender (LGBT), International Law, National Law * Student of Department of International Law ** First Advisor of Faculty of Law, University of North Sumatra *** Second Advisor Faculty of Law, University of North Sumatra